Fitrah Based Education: Implementasi Manajemen Pendidikan Berbasis Fitrah di TK Adzkia Banjarnegara - Musfiatul Muniroh (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2019)
This research aims to describe the educational management based on fitrah in Kindergarten (TK) ‘Adzkia’ Banjarnegara. This research uses descriptive qualitative method. Data sources are obtained through observation, interviews and documentation involving the principal, teachers and the guardians of the students. The results of the research showed that the educational management based on fitrah in TK Adzkia Banjarnegara is implemented by developing the character of ideal exemplary, logical reasoning and creativity, leadership and entrepreneurship. There are 18 Adzkia attitudes that are internalized in the process of education, namely respect, honesty, quality, cleanliness, affection, patience, love, sincerity, discipline, responsibility, devotion, diligence, positive thinking, hospitality, modesty, Qonaah, Taqwa and Istiqomah. These attitudes were developed with fitrah-based education that includes individual, social, societal, logical, learning, and physical development. The inculcation of attitudes and fitrah is carried out by applying Beyond Centers and Circle Time (BCCT) method, stimulating multiple intelligences, implementing Emotional-Spiritual Quotions and Neuroscience ideas. The implementation of educational management based on fitrah is supported by the Education Office, local government, school committee and parents. However, some parents do not have complete understanding of the fitrah-based education thereby the learner’s potential has not appeared to the fullest.